'War on terror' and the framework of international law - Duffy, Helen (UK, CUP, 2015)
"Acts of international terrorism, such as the atrocities committed on 11 September 2001 ('9/11') and others since then, highlight the critical importance of the international rule of law and the terrible consequences of its disregard. Ultimately, however, the impact of such attacks depends on the responses to them, and in turn on the reaction to those responses. To the extent that the lawlessness of terrorism is met with unlawfulness, unlawfulness with impunity, the long-term implications for the rule of law, and the peace, stability and justice it serves, will be grave"--
Includes bibliographical references (pages 938- 965) and index.
Keywords: War on Terrorism, 2001-2009.; War (International law); POLITICAL SCIENCE / Political Freedom & Security / Human Rights